Association Between Diabetes and Cancer Risk: A Rapid Review of Cohort Studies Published Since 2013 to 2024. - Phoseka, Sinelile; Jaya, Ziningi; Thembane, Nokukhanya (Student’s Journal of Health Research Africa, 2025)
Background Diabetes mellitus (DM) and cancer are two prevalent and debilitating health conditions worldwide. Emerging evidence suggests that diabetes not only increases the risk of developing various cancers but may also worsen cancer progression and complicate treatment outcomes. This rapid review evaluates existing cohort studies that investigate the progression from diabetes to cancer, with a focus on identifying key factors that potentially influence cancer development in diabetic patients. Methods 25 cohort studies from 2013-2024 sourced from Google Scholar, including prospective, retrospective, and clinical studies examining the relative risk of various cancers in diabetic populations were reviewed. The quantitative cancer risk analyses conducted on people with diabetes in these studies were also reviewed. Studies that did not report risk estimates and studies with cross-sectional or case-control designs were excluded. Results The review showed a gradual increase in the number of studies investigating the relationship between diabetes and cancer, with the highest proportion conducted between 2021 (16%) and 2023 (12%). Findings revealed an association of Type 2 DM (T2DM) with a higher risk of pancreatic cancer (OR = 2.50) and colorectal cancer in men (HR = 1.42). Standardized risk ratios (SRR) revealed stronger associations of T2DM with certain cancers, including endometrial cancer (SRR = 1.81). Conclusion When compared with Type 1 DM, T2DM is associated with a higher risk of cancer including pancreatic, colorectal, endometrial, and breast cancers. Obesity, glycaemic control, disease duration, and the effects of therapeutic treatment have been highlighted as factors that contribute to this increased risk. Furthermore, the study emphasizes the importance of tailored approaches to cancer risk management in diabetes patients, considering gender, region, and treatment techniques. Recommendations Future research should investigate the link between diabetes and cancer, emphasizing underexplored cancer types, diabetes medications, gender, region, and socioeconomic status to enhance cancer prevention in diabetic populations.